2008
DOI: 10.1038/sj.jid.5701189
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin-3-Deficient Mice Develop Hair Coat Abnormalities and Are Prone to Cutaneous Inflammation

Abstract: We generated mice deficient in plakophilin-3 (PKP3), a member of the Armadillo-repeat family and a component of desmosomes and stress granules in epithelial cells. In these mice, several subsets of hair follicles (HFs) had morphological abnormalities, and the majority of awl and auchene hair shafts had fewer medullar air columns. Desmosomes were absent from the basal layer of the outer root sheath of HFs and from the matrix cells that are in contact with dermal papillae. In the basal layer of PKP3-null epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 42 publications
(44 reference statements)
7
75
0
Order By: Relevance
“…Recently a new syndrome featuring severe dermatitis, multiple allergies, and metabolic wasting (SAM syndrome) caused by homozygous mutations in DSG1 supports the hypothesis that impaired epidermal barrier function may also contribute to the development of infl ammatory skin diseases (Samuelov et al, 2013). Data from mice defi cient in plakophilin-3 (PKP3), a member of the Armadillo-repeat family, and a component of desmosomes also strongly supports this hypothesis (Sklyarova et al, 2008). In the basal layer of PKP3-null epidermis, densities of desmosomes, and AJs were remarkably altered.…”
Section: Desmosomes and Keratin Network In Skin Inflammationsupporting
confidence: 48%
See 1 more Smart Citation
“…Recently a new syndrome featuring severe dermatitis, multiple allergies, and metabolic wasting (SAM syndrome) caused by homozygous mutations in DSG1 supports the hypothesis that impaired epidermal barrier function may also contribute to the development of infl ammatory skin diseases (Samuelov et al, 2013). Data from mice defi cient in plakophilin-3 (PKP3), a member of the Armadillo-repeat family, and a component of desmosomes also strongly supports this hypothesis (Sklyarova et al, 2008). In the basal layer of PKP3-null epidermis, densities of desmosomes, and AJs were remarkably altered.…”
Section: Desmosomes and Keratin Network In Skin Inflammationsupporting
confidence: 48%
“…In the basal layer of PKP3-null epidermis, densities of desmosomes, and AJs were remarkably altered. PKP3-null mice were prone to dermatitis providing in vivo evidence that PKP3 plays a critical role in limiting infl ammatory responses in the skin (Sklyarova et al, 2008).…”
Section: Desmosomes and Keratin Network In Skin Inflammationmentioning
confidence: 99%
“…However, PKP2 KO mice died around day 11.5 of embryonic development because of heart defects, indicating that at least one PKP is required for stable intercellular adhesion (Grossmann et al 2004). In contrast, PKP3 2/2 mice were viable but developed hair abnormalities and increased inflammation of the skin, manifest in mice kept in a nonpathogen-free environment (Sklyarova et al 2008). We have recently shown that PKP1 is essential for epidermal integrity in vivo.…”
Section: Evidence From Mouse Models and Human Diseasesmentioning
confidence: 96%
“…Although no human pathologies are associated with mutations in PKP3, conditional ablation of PKP3 in mouse epidermis resulted in defective hair follicle morphogenesis, increased keratinocyte proliferation, and desmoplakin mislocalization. These mice are also more susceptible to dermatitis (skin inflammation) and secondary alopecia (hair loss) (Sklyarova et al 2008).…”
Section: Plakophilinsmentioning
confidence: 99%